USE OF SONGS IN THE TEACHING ENGLISH CLASSROOM - Абдрахманов, А.К. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
This article focuses on the use of songs in teaching English as a foreign language. Various types of activities are shown, both for strong classes and for beginners, using the “listening” stages. Each activity describes the teacher’s instructions and the feedback of the students, as well as an example from a textbook from Express Publishing.
Keywords: songs; listening; Express Publishing; activity; approaches with te use of songs